Three Stages of Modern Science - Bauer, Henry (Journal of Scientific Exploration, 2013)
The common view of science is a misunderstanding of today's science that does not recognize how "modern" science has changed since its inception in the 16th to 17th centuries. Science is generally taken to be objectively reliable because it uses "the scientific method" and because scientists work disinterestedly, publish openly, and keep one another honest through peer review. That common view was not too unrealistic in the early days and the glory days of modern science, but it is quite wrong about contemporary science, which has ceased to be trustworthy because it is subject to commercial and bureaucratic influences that have spawned highly damaging conflicts of interest, institutional as well as personal. The birth of "modern" science is credited uncontroversially to "The" Scientific Revolution of the 17th century, but it has not been widely under-stood that there have been three distinctly different stages of scientific activity since then. In the first stage, amateurs were seeking to satisfy their curiosity about how the world works. There were essentially no controlling interests other than truth-seeking. Missteps taken resulted chiefly from the inherent difficulty of making discoveries and from such inherent human flaws as pride and avarice. The second stage, roughly the 19th century, saw science becoming a career, a plausible way to make a living, not unlike other careers in academe or professions like engineering: respectable and potentially satisfying but not any obvious path to great influence or wealth. Inevitably there were conflicts of interest between furthering a career and following objectively where evidence pointed, but competition and collegiality served well enough to keep the progress of science little affected by that conflicting career interest. The way to get ahead was by doing good science. In the third and present stage, which began at about the middle of the 20th century, science faces a necessary change in ethos as its centuries-long expansion at an exponential rate has changed to a zero-sum, steady-state situation that has fostered intensely cutthroat competition. At the same time, the record of science's remarkable previous successes has led industry and government to co-opt and exploit science and scientists. Those interactions offer the possibility for individuals to gain considerable public influence and wealth. That possibility tempts to corruption. Outright fraud in research has become noticeably more frequent, and public pronouncements about matters of science are made for self-interested bureaucratic and commercial motives. The public cannot now rely safely on the soundness of advice from the scientific community. Keywords: historical changes in science, science become untrustworthy